2021
DOI: 10.1017/ice.2021.413
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clostridioides difficile infection on patient-reported quality of life

Abstract: Objective: We investigated the quality of life (QoL) of patients hospitalized with C. difficile infection (CDI). Design: Prospective survey study. Setting: US tertiary-care referral center, acute-care setting. Participants: Adults hospitalized with a diagnosis of CDI, defined as ≥3 episodes of unformed stool in 24 hours and a positive laboratory test for C. difficile. Methods: We surveyed patients from July 2019 to March 2020 using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…Policy makers and clinical practice guidelines recognize patient-reported outcomes as important endpoints in clinical research and practice [ 8 ]. Consequently, health-related quality of life (HrQOL) measures seem particularly important in patients with CDI [ 3 , 5 , 10 ]. There are different generic tools created for patient-reported outcomes [ 11 ] and quality of life [ 4 7 ], however, Cdiff32 is the only instrument specifically developed to assess HrQOL in patients with CDI [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Policy makers and clinical practice guidelines recognize patient-reported outcomes as important endpoints in clinical research and practice [ 8 ]. Consequently, health-related quality of life (HrQOL) measures seem particularly important in patients with CDI [ 3 , 5 , 10 ]. There are different generic tools created for patient-reported outcomes [ 11 ] and quality of life [ 4 7 ], however, Cdiff32 is the only instrument specifically developed to assess HrQOL in patients with CDI [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The strength of this study includes a sizeable cohort as this is the second largest study to date demonstrating quantitative changes of patient-reported HrQOL in CDI [ 3 6 , 10 ]. In addition, the current study had rigorous individual patient follow-up providing HrQOL data at two different time points.…”
Section: Discussionmentioning
confidence: 99%
“…The panel's heavy emphasis on the avoidance of recurrent CDI is supported by data suggesting that patients with recurrent disease suffer from poorer quality of life. 3 However, several counterarguments can be made with respect to the new recommendations, including increased financial consequences to the patient and health system. Regarding increased costs to the individual, a recent study of Medicare enrollees showed that only 1.1% had access to fidaxomicin and 14.4% had access to vancomycin as a tier 1 or tier 2 medication.…”
Section: Concerns With Recommendation Changesmentioning
confidence: 99%
“…Furthermore, CDI prolongs hospitalizations, and recent evidence suggests that recurrent and more severe disease are associated with lower quality of life. 3 In 2021, the Infectious Diseases Society of America (IDSA), in collaboration with the Society for Healthcare Epidemiology of America (SHEA), published a focused update with specific recommendations for the treatment of initial CDI, recurrent CDI, and the role of bezlotoxumab. 4 In this article, we review the major recommendation updates, highlight the ethical and clinical dilemmas arising from them, and suggest a principlist approach to addressing these recommendations on individual, programmatic, and healthcare system levels.…”
mentioning
confidence: 99%
“…They often feel depressed and may be in isolation, cutting them off from friends and family. 30 We should not forget that in older patients, diarrhoea often leads to incontinence. This is terrible for the individual's self-respect, and they worry about developing a chronic illness.…”
Section: For Patients At High Risk Of Clostridioides Difficile Recurr...mentioning
confidence: 99%